Evaluation of Students’ Knowledge and Pattern towards Vitamin D (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Background: Several previous studies revealed an indicator of a high vitamin D deficiency rate in society groups, so this investigation aimed to verify the university students’ knowledge about the significance of vitamin D in their lives.Method: A questionnaire was used, including a set of questions about the information and significance of vitamin D among the 547 students of Hilla University College of different ages.Results: This study evaluated university students' knowledge of vitamin D (V-D), as it illustrated that half of the students know about vitamin D deficiency, and their percentage was 49.8%, while 74.9% of students detect that the leading V-D source is sun, and this agrees with previous studies. Interestingly, (72.6%) of the people knew the sun as the primary V-D source. The findings clearly illustrated that there is shortage knowledge among students about V-D. It was found that most of the participants knew that a Deficiency of V-D is related to diseases Bones and osteoporosis. However, they did not know that V-D is also linked to other health problems.Conclusion: More knowledge and practice regarding V-D need to be provided, which can be reduced by promoting awareness of V-D in society groups, especially university students.